Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I have to use

$$\sum_{n=1}^{\infty}\frac{(-1)^{n+1}}{n}=\log 2$$

to compute

$$\sum_{n=1}^{\infty}\frac{(-1)^{n}}{n(n+1)}$$

Since,

$$\sum_{n=1}^{\infty}\frac{(-1)^{n}}{n(n+1)} = \sum_{n=1}^{\infty}\frac{(-1)^{n}}{n}-\sum_{n=1}^{\infty}\frac{(-1)^{n}}{(n+1)}$$

Now, $$\sum_{n=1}^{\infty}\frac{(-1)^{n}}{n} = \ -log 2 $$

$$\sum_{n=1}^{\infty}\frac{(-1)^{n}}{(n+1)} = \log 2 -1 $$

Hence , the answer seems to be $1 - 2 \log 2$.

share|improve this question
4  
Hint: $\frac1{n(n+1)}=\frac1n-\frac1{n+1}$. –  Did May 17 '12 at 20:46
add comment

2 Answers 2

up vote 3 down vote accepted

Noting that

$$\frac{1}{n(n+1)}=\frac{1}{n}-\frac{1}{n+1}$$

we have

$$\sum_{n=1}^{\infty}\frac{(-1)^{n}}{n(n+1)}= \sum_{n=1}^{\infty}\left(\frac{(-1)^{n}}{n}-\frac{(-1)^{n}}{n+1}\right)$$

The first part is obviously $-\log 2$ (from the definition above), so we have

$$\sum_{n=1}^{\infty}\left(\frac{(-1)^{n}}{n}-\frac{(-1)^{n}}{n+1}\right) =-(\log 2+\sum_{n=1}^{\infty}\frac{(-1)^{n}}{n+1})$$

I'm sure you can take it from here (a substitution may help).

share|improve this answer
    
I am guessing the $-1$ was for the fact that you need justification for $\sum_{n=1}^{\infty}\left(\frac{(-1)^{n}}{n}-\frac{(-1)^{n}}{n+1}\right) =-(\log 2+\sum_{n=1}^{\infty}\frac{(-1)^{n}}{n+1})$ and is a common mistake students make. (I didn't upvote, in case you are wondering). –  Aryabhata May 17 '12 at 21:04
1  
@Aryabhata Which $-1$ are you referring to? –  Argon May 17 '12 at 21:05
    
Someone downvoted this answer, and for a valid reason. –  Aryabhata May 17 '12 at 21:13
    
@Argon: Thanks for your reply. Can you please verify the solution. –  preeti May 17 '12 at 21:15
6  
@Argon: You seem to miss the point I was trying to make. It is about justifying $\sum_{n=1}^{\infty} (a_n - b_n) = \sum_{n=1}^{\infty} a_n - \sum_{n=1}^{\infty} b_n$. For instance $0 = \sum_{n=1}^{\infty} (1/n - 1/n) = \sum_{n=1}^{\infty} 1/n - \sum_{n=1}^{\infty} 1/n$ might be meaningless. Of course, that is just my guess as to why you got a downvote. In your case, both $\sum a_n$ and $\sum b_n$ converge so it is not a problem. –  Aryabhata May 17 '12 at 21:41
show 4 more comments

HINT:

Consider partial fraction decomposition.

share|improve this answer
1  
Thanks for the hint. –  preeti May 17 '12 at 21:15
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.